(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2022)
The work is part of the research project ‘Teaching and learning of social and human sciences from an interdisciplinary perspective and approach to social problems’. We present the analysis of the information and data obtained from a questionnaire completed by teachers from the area of ​​various schools in Río Negro and Neuquén, Argentina. Our objective is to identify and analyze the treatment of social problems carried out by the Social and Human Sciences teachers and how they contribute to the development of social thinking in high school students from two provinces of North Patagonia, from an interdisciplinary approach. Within this framework, we share the assessments made by teachers on interdisciplinary work in the area, the social problems they select to organize their teaching proposals and the perspectives that guide the conceptions of social problems and interdisciplinarity.